Requirements Analysis and Proposed Model for a Wireless Network Infrastructure in Bukit Kachi Student College, UUM - Mohd. Yusuf, Md. Saad (2005)
This project has analysed the requirements and needs, as well as proposed a few solution models for implementing a wireless local area network (WLAN) infrastructure for network and Internet access for students and staff alike, at the Bukit Kachi Residential College, Universiti Utara Malaysia. The study covers technological aspects as well as the required hardware for a successful WLAN installation, location investigation, student capacity and usage, as well as the basic applications used by students and staff to access the network. Financial comparisons between WLAN and wired networks, as well as the advantages and disadvantages of the two networks are emphasised in this study. WLAN is widely accepted these days because much research and implementation have been carried out over the past couple of years at the university level. Today, communication channels and information retrieval is of utmost importance for tertiary education, since much of the resulting work stems from or is associated with information technology (IT), which is expanding, rapidly, seemingly without boundaries. With the installation of a network access, many services can be launched, including an electronic library, electronic research and learning, as well as administrative work carried out by an organisation such as the university. In line with the current needs in tertiary education which obviously leans towards wireless technology, the university administration should initiate and continue to improve wireless network technology to fulfill the needs of the campus community as an alternative to the current wired technology. Several reasons to do so include the open aspect of such a technology, improved work processes, differences in installation and maintenance costs, and other advantages that will tie discussed in this report. From the analysis, it was observed that an implementation of a WLAN at the college is a good step in preparing a suitable, if not optimal, study environment for the students, and improve the work processes of the current staff. Such a system will save time in installation and maintenance, which in turn will save money. This wireless system will also provide a wide coverage that will free the students from being restricted to their rooms and computer laboratories, as well as remove any time restrictions associated with using the traditional wired access. In short, a WLAN will enable the students to gather information and communicate anytime, and anywhere within coverage.